Developing Wood Dust Into Horta Dolls to Develop Language Aspects in Children Aged 4-5 Years - Fauziah, Lailul; Mahmudah, Masrurotul; Dea, Leli Fertiliana; Utama, Ferdian; Setiawan, Agus (Bulletin of Pedagogical Research, 2024)
This research discusses the language aspect abilities of children aged 4-5 years, because the language aspect abilities at RA Wajar Fantri Bakti Sumber Baru are still relatively undeveloped. So researchers took the initiative to develop horta media to overcome this problem. The aim of this research is to determine the development and effectiveness of Horta doll media to improve the language skills of children aged 4-5 years. This research is R&D research using the Borg and Gall theory R&D model. Data collection methods are observation, interviews, documentation and questionnaires. The results of this research are as follows: The language abilities of children aged 4-5 years at RA Wajar Fantri Bakti Sumber Baru for the 2023/2024 academic year have developed well, this can be seen from the language ability indicators which consist of: First, listening to what people say other. Based on the results of research from 24 children, there were 23 children who listened well to the teacher's words, while the remaining 1 child did not pay attention to the teacher. Second, understand two commands given simultaneously. Of the 24 children, 20 were able to understand and carry out two commands simultaneously, while the other 4 children only carried out one command. Third, understand the story being read. Of the 24 children, 22 children understood the story that was read, while the other 2 children still did not understand the content of the story. Third, get to know the vocabulary regarding adjectives. Of the 24 children, 21 children began to recognize all the adjectives that had been taught, namely naughty, stingy, kind, brave, good, bad, while the remaining 3 children only knew some of these adjectives. Fifth, hear and differentiate sounds in Indonesian. Based on the research results, there were 20 children who were able to differentiate sounds while the remaining 4 children still had difficulty distinguishing these sounds. The remaining 4 children still have difficulty distinguishing these sounds. Keywords: Learning Media, Horta Dolls, Developing Language Ability